Mixed Epithelial and Stromal Tumor of the Kidney with Extension into Inferior Vena Cava: Case Report and Discussion of Adult Biphasic Cystic Renal Lesions and the Significance of Vascular Involvement - Maria M. Picken; Davide Bova; Michael R. Pins; Marcus L. Quek (Hindawi Limited, 2018)
Mixed epithelial and stromal tumor (MEST) is a biphasic adult renal lesion composed of solid and cystic areas containing spindle cell stroma and epithelium that lines the tubules and cystic spaces. While most MEST lesions are benign, rare cases with malignant morphology and biology have been reported. We present a case of mixed epithelial and stromal tumor of the kidney (MEST) with extension into the inferior vena cava in a young adult male. We discuss the differential diagnosis of MEST in the context of other biphasic cystic renal lesions and the significance of vascular involvement in the setting of an otherwise benign tumor morphology.